STUDY OF PROTEIN AND LIPID CONTENTS IN SELECTED TISSUES OF MALE ALBINO RATS UNDER NOVEL HETEROCYCLIC COMPOUND TOXCITY - KUMAR, M. ANIL; KRISHNAREDDY, M.; SARANGAPANI, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The present study was carried out on the effect of 3-Imino -(2-Oxo-3,4-Dihydro-4-Phenyl-5- Carboethoxy-6-Methyl-Pyrimidine-3yl)-5-Chloro-Indole-2-Ones compound on total proteins, free amino acids and total lipid contents in testis, brain, heart, kidney and liver of male albino rats. Levels of total proteins were decreased, while free amino acids and total lipid contents were increased in Selected tissues of treated rats.